The Influence of Transformational Leadership and Organizational Culture on Job Satisfaction and Organizational Citizenship Behavior (OCB) in Islamic Educational Institutions - Mastur, Mastur; Soim, Soim; Haryanti, Nik; Gufron, Moh (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This paper examines the effect of transformational leadership and organizational culture on organizational citizenship behavior (OCB), with job satisfaction as an intervening variable. A quantitative approach is used to examine the relationship or influence between (X), (Y), and (Y1). The population in this study was 50 respondents. The results showed a significant partial effect of the transformational leadership variable on job satisfaction. The organizational culture variable has a partially significant influence on job satisfaction. The transformational leadership variable has a partially significant influence on organizational citizenship behavior. There is no significant partial effect of organizational culture on organizational citizenship behavior. This study has implications for the importance of cultural awareness of organizational citizenship behavior for each individual to build a good work team so that the achievement of organizational performance can be better than before.